Screening for psychological distress in adult primary brain tumor patients and caregivers: considerations for cancer care coordination - Wafa eTrad; Eng-Siew eKoh; Eng-Siew eKoh; Maysaa eDaher; Maysaa eDaher; Alanah eBailey; Marina eKastelan; Marina eKastelan; Dianne Maree Legge; Marcia eFleet; Grahame Kenneth Simpson; Grahame Kenneth Simpson; et al. (Frontiers in Oncology, 2015)
IntroductionThis study aimed to assess psychological distress (PD) as scored by the Distress Thermometer (DT) in adult primary brain tumor (PBT) patients and caregivers in a clinic setting, and ascertain if any high risk sub-groups for PD exist. Material and MethodsFrom May 2012 to August 2013, n=96 patients and n=32 caregivers (CG) underwent DT screening at diagnosis, and a differing cohort of n=12 patients and n=14 caregivers at first recurrence. Groups were described by diagnosis (high grade, low grade and benign), and English versus non-English speaking. Those with DT score≥4 met caseness criteria for referral to psycho-oncology services. One-way ANOVA tests were conducted to test for between group differences where appropriate.ResultsAt diagnosis and first recurrence, 37.5% and 75.0% (respectively) of patients had DT scores above the cut-off for distress. At diagnosis, 78.1% of caregivers met caseness criteria for distress. All caregivers at recurrence met distress criterion. Patients with high grade glioma had significantly higher scores than those with a benign tumor. For patients at diagnosis, non-English speaking participants did not report significantly higher DT scores than English speaking participants.DiscussionPsychological distress is particularly elevated in caregivers, and in patients with high grade glioma at diagnosis. Effective PD screening, triage and referral by skilled care coordinators is vital to enable timely needs assessment, psychological support and effective intervention.